Success of Implantable Doppler Probes for Monitoring Buried Free Flaps. (22nd February 2022) - Dunklebarger, Mitchell Frye; McCrary, Hilary; King, Brody; Carpenter, Patrick; Buchmann, Luke; Hunt, Jason; Cannon, Richard
Abstract : Objective: The objective of this study is to describe the operative success of completely buried free flaps and to determine the safety/reliability of using implantable dopplers for postoperative monitoring in completely buried free flaps. Study Design: A retrospective chart review was conducted from 2014 to 2020. Patients were included who had implantable dopplers placed for monitoring a completely buried free flap without a visible skin paddle. Setting: Single academic cancer hospital. Methods: Patient charts were reviewed to determine flap viability after surgery, need for reoperation, and ability of implanted doppler probes to detected change in free flap status. Results: A total of 65 patients were included. Locations of flaps were as follows: pharynx, 76.9%; skull base, 7.7%; trachea, 6.2%; esophagus, 4.6%; and facial reanimation, 4.6%. Types of free flaps performed included radial forearm (50.8%), anterolateral thigh (44.6%), and gracilis (4.6%). One patient (1.5%) returned to the operating room for vascular compromise,  which was accurately detected by the implantable doppler and salvaged. All free flaps were viable upon hospital discharge based on clinical examination and implantable doppler signals. There were no complications related to implantable doppler use. Conclusions: Implantable dopplers are an effective method for evaluating postoperative success of completely buried free flaps. In our series utilizing implantable dopplers, buried free flap survival was higher than traditionally thought. The use of implanted dopplers for monitoring buried free flaps allows for an effective, cosmetically appealing, and simplified reconstructive technique.